Modal Sosial Kyai dalam Penguatan Mitigasi Bencana Rob pada Masyarakat Pesisir Desa Purwosari Demak - Sellya Saraswati Dewi; Fulia Aji Gustaman (Universitas Hamzanwadi, 2026)
Tidal flooding has become an increasingly prevalent phenomenon due to climate change and has significant impacts on the social and economic activities of coastal communities. The intensity of recurring tidal flooding events causes increased vulnerability and requires a mitigation strategy that not only focuses on physical aspects (hard structure), but also emphasizes the development of understanding (soft structure). This study aims to analyze the role of the Kyai’s social capital in mitigating tidal flood disasters through enhancing community understanding in Purwosari Village. This research employs a qualitative approach with a case study method to gain an in-depth understanding of the social dynamics within the community. Data collection techniques include observation, documentation, and in-depth interviews with informants selected based on specific criteria, namely the Kyai of Purwosari Village, disaster preparedness analysts from the Regional Disaster Management Agency (BPBD), and the Purwosari community. The data were analyzed using thematic analysis techniques. The results of the study indicate that Kyai plays a strategic role in conveying disaster mitigation messages through a religious approach based on trust, social networks, and norms. This form of social capital contributes to shaping collective awareness in protecting the environment and strengthening social solidarity in the community in facing tidal flooding. Furthermore, the community develops various adaptive strategies in response to continuously changing environmental conditions. Thus, soft structure based mitigation through the Kyai’s social capital contributes to enhancing the adaptive capacity and resilience of the Purwosari Village community to tidal flood disasters.